2013
DOI: 10.1007/8904_2013_229
|View full text |Cite
|
Sign up to set email alerts
|

Selective Screening for Lysosomal Storage Diseases with Dried Blood Spots Collected on Filter Paper in 4,700 High-Risk Colombian Subjects

Abstract: Lysosomal storage disorders (LSDs) are a very heterogeneous group of hereditary disorders. The diagnostic process usually involves complex sampling, processing, testing, and validation procedures, performed by specialized laboratories only, which causes great limitations in reaching a diagnosis for patients affected by these diseases.There are few studies about LSDs in Colombia. The diagnostic limitations often make medical practitioners disregard the possibility of these disorders while diagnosing their patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
2
22
0
12
Order By: Relevance
“…The prevalence of males with Fabry disease ranges from 1:17,000 to 1:117,000 in the Caucasian population 4, 5. Recent newborn screening studies have, however, indicated a much higher incidence of this disorder because patients with later onset and milder forms of Fabry disease are found even more commonly than expected, suggesting that they are possibly underdiagnosed 6, 7, 8, 9, 10, 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of males with Fabry disease ranges from 1:17,000 to 1:117,000 in the Caucasian population 4, 5. Recent newborn screening studies have, however, indicated a much higher incidence of this disorder because patients with later onset and milder forms of Fabry disease are found even more commonly than expected, suggesting that they are possibly underdiagnosed 6, 7, 8, 9, 10, 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…For dried blood spot (DBS) samples, we evaluated the same group of patients, but the DBS activity values were compared with their reported reference values. 11…”
Section: Methodsmentioning
confidence: 99%
“…Both methods for evaluation of BGal used the same fluorogenic substrate (4-methylumbelliferyl-ÎČ-D-galactoside) and incubation buffer (citrate-phosphate). The DBS samples were analyzed by duplicate according to the method described by Uribe and Giugliani, 11 and the enzymatic activities were expressed as nanomol of substrate hydrolyzed per milliliter of sample per hour (nmol/mL/h). Here milliliters are calculated in accordance to what Uribe and Giugliani 11 described for DBS punches of 1.2 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such context, development of high-throughput methods for enzyme analysis using DBSs [49] or the analysis of GAG species in urine samples [50] made feasible the possibility of newborn screening programs for MPS diseases, in particular, for MPS I, II and VI where there is possibility of therapy with bone marrow transplant and/or ERT. At the moment, some pilot programs have been developed that probably will have great impact in the current management of MPS patients since early therapeutic strategies could be offered for such patients [51,52].…”
Section: Expert Opinionmentioning
confidence: 99%